Potential mitigation contribution from coffee agroforestry in three regions of Viet Nam - Pham, Van Thanh; Mulia, Rachmat; Dinh, Hang Thu (World Agroforestry Centre, 2018)
Coffee agroforestry is one of the main agroforestry systems in Viet Nam in terms of total land area in the country, potential economic contribution, and ecosystem services provided by the shading tree species in the system. This report presents the results of a study that aimed to estimate potential mitigation contribution from carbon storage from coffee agroforestry systems in the three regions of the country. The estimated C storage of arabica coffee systems in the Northwest region of Viet Nam ranges from 2.6 to 17.0 ton ha-1. Potential storage at province level reaches 246,224 ton in Son La province, as it has a higher total area of coffee plantations than Dien Bien province. In the Southeast and Central Highlands region, the estimated C storage of robusta and arabica coffee agroforestry systems ranges from 5.8 to 10.4 ton ha-1, in general due to variation in shading tree species and density. The potential C storage at province level can reach up to 2.1 million ton as in the case of Dak Lak province. From local interviews with provincial authorities and smallholder farmers in the three regions, stakeholders could see the economic and environmental benefits that can be derived from the coffee agroforestry systems. However, the lack of knowledge in planting design and plot management options constrain farmers from transforming their coffee monoculture into agroforestry systems, or expanding the system into available areas for coffee cultivation. We recommend that the provincial authorities keep supporting and encouraging research on coffee agroforestry and provide reliable technical guidance for farmers to develop coffee agroforestry systems with appropriate design.